ANALISIS PENERAPAN METODE PENYUSUTAN AKTIVA TETAP DALAM PENENTUAN LABA PADA PT. TELAGA ENDE - Sombo, Yosephina Mentalin; Londa , Yulita; Kapa , Sesilianus (Jurnal Riset Ilmu Akuntansi, 2020)
The application of the method for each type of fixed assets in accordance with PSAK No. 16 will increase profits in the company. This study aims to determine the application of the method of depreciation of fixed assets at PT. Ende Lake. The application of the depreciation method for fixed assets at PT. Telaga Ende using the straight line method yields a profit of 0.015951% compared to using the multiple declining balance method and the straight-line depreciation method is 0.007838% higher than the number of years. Suggestion, to increase profit on the depreciation of fixed assets at PT. Telaga Ende companies should use the depreciation method for each type of fixed assets in accordance with PSAK No. 16.